Brief Report: A Polymorphism in TLR2 Is Associated With Arterial Thrombosis in a Multiethnic Population of Patients With Systemic Lupus Erythematosus1. Issue 7 (July 2014) - Kaiser, Rachel; Tang, Ling Fung; Taylor, Kimberly E.; Sterba, Kirsten; Nititham, Joanne; Brown, Elizabeth E.; Edberg, Jeffrey C.; McGwin, Gerald; Alarcón, Graciela S.; Ramsey‐Goldman, Rosalind; Reveille, John D.; Vilá, Luis M.; et al.
<x xml:space="preserve">Abstract</x> Objective Thrombosis is a serious complication of systemic lupus erythematosus (SLE). Studies that have investigated the genetics of thrombosis in SLE are limited. We undertook this study to assess the association of previously implicated candidate genes, particularly Toll‐like receptor (TLR) genes, with pathogenesis of thrombosis. Methods We genotyped 3, 587 SLE patients from 3 multiethnic populations for 77 single‐nucleotide polymorphisms (SNPs) in 10 genes, primarily in TLRs 2, 4, 7, and 9, and we also genotyped 64 ancestry‐informative markers (AIMs). We first analyzed association with arterial and venous thrombosis in the combined population via logistic regression, adjusting for top principal components of the AIMs and other covariates. We also subjected an associated SNP, rs893629, to meta‐analysis (after stratification by ethnicity and study population) to confirm the association and to test for study population or ethnicity effects. Results In the combined analysis, the SNP rs893629 in the KIAA0922/TLR2 region was significantly associated with arterial thrombosis (logistic P = 6.4 × 10−5, false discovery rate P = 0.0044). Two additional SNPs in TLR2 were also suggestive: rs1816702 (logistic P = 0.002) and rs4235232 (logistic P = 0.009). In the meta‐analysis by study population, the odds ratio (OR) for arterial thrombosis with rs893629 was 2.44 (95% confidence interval 1.58–3.76), without evidence for heterogeneity (P = 0.78). By ethnicity, the effect was most significant among African Americans (OR 2.42, P = 3.5 × 10−4) and European Americans (OR 3.47, P = 0.024). Conclusion TLR2 gene variation is associated with thrombosis in SLE, particularly among African Americans and European Americans. There was no evidence of association among Hispanics, and results in Asian Americans were limited due to insufficient sample size. These results may help elucidate the pathogenesis of this important clinical manifestation.